2018
DOI: 10.1007/s12560-018-9345-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Winter Relocation and Depuration on Norovirus Concentrations in Pacific Oysters Harvested from a Commercial Production Site

Abstract: Oysters contaminated with norovirus present a significant public health risk when consumed raw. In this study, norovirus genome copy concentrations were determined in Pacific oysters (Magallana gigas) harvested from a sewage-impacted production site and then subjected to site-specific management procedures. These procedures consisted of relocation of oysters to an alternative production area during the norovirus high-risk winter periods (November to March) followed by an extended depuration (self-purification)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These results are consistent with both laboratory-based depuration studies and commercial-based depuration studies, which evidenced a two-phase depuration kinetics in many mollusk species, although with different timing in the different species [ 10 , 16 , 31 ], probably due to the variability among species and the capability of NoV to resist to suboptimal conditions during depuration process, as suggested by other authors [ 14 , 16 ]. In several studies on oysters, indeed, a maximum viral reduction was obtained in the first 3–4 days of depuration, while no further significative reduction was observed by extending the time [ 26 , 32 ]. Some authors suggest that the more rapid viral reduction in the first phase could be related to extracellular digestion and purging of the digestive tract, while in the second phase, viral reduction is more difficult and slower because NoV is specifically attached to ligands present on oysters’ gastrointestinal cells or in other parts outside the digestive tract lumen, like hemocytes [ 17 , 20 , 23 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with both laboratory-based depuration studies and commercial-based depuration studies, which evidenced a two-phase depuration kinetics in many mollusk species, although with different timing in the different species [ 10 , 16 , 31 ], probably due to the variability among species and the capability of NoV to resist to suboptimal conditions during depuration process, as suggested by other authors [ 14 , 16 ]. In several studies on oysters, indeed, a maximum viral reduction was obtained in the first 3–4 days of depuration, while no further significative reduction was observed by extending the time [ 26 , 32 ]. Some authors suggest that the more rapid viral reduction in the first phase could be related to extracellular digestion and purging of the digestive tract, while in the second phase, viral reduction is more difficult and slower because NoV is specifically attached to ligands present on oysters’ gastrointestinal cells or in other parts outside the digestive tract lumen, like hemocytes [ 17 , 20 , 23 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oyster producers need effective virus reduction measures in order to meet any such microbiological criterion for norovirus in the future. Previously, we demonstrated the potential of risk management procedures to reduce the risk of norovirus contamination in a production area as well as the reduction of norovirus concentrations in end-product by depuration (Rupnik et al 2018 ). In that particular study extended depuration periods of up to 9 days were applied during the high-risk winter season.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have indicated that depuration time and seawater temperature are both factors that may influence virus reduction during bivalve shellfish depuration (Lees et al 2010). The potential for norovirus reduction in oysters during enhanced depuration procedures was identified previously by this group (Rupnik et al 2018) prompting this study to investigate norovirus reduction in oysters under controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations